INVESTIGATING THE LEVEL OF STUDENT LEARNING STRATEGIES IN PHYSICS COURSES THROUGH THE LASSI INSTRUMENT - Ilham Akbar (Journal of Teaching and Learning Physics, 2023)
Learning strategy is a strategy needed by students to gain academic achievement effectively and efficiently. Students who have a high level of learning strategies (> 75%) have greater potential for academic success. As in this study which aims to analyze the level of student learning strategies in physics courses through the LASSI instrument. The LASSI instrument is used to diagnose the level of learning strategies which include three main components, namely the skill, will, and self-regulated components. Each of the three components has essential subscales including anxiety, attitude, motivation, concentration, information processing, time management, test-strategy, self-testing, study aids, and selection of main ideas. Miles and Huberman's technique is used as a technique in data analysis. The number of respondents included in this study were 65 students, consisting of 38 second semester students of the mathematics education study program, 17 students of the fourth semester of the mathematics education study program, and 10 extension students of the sixth semester of the mathematics education study program. The level of student learning strategies can be categorized into three levels (levels) of student learning strategies as follows: for the 2018/2019 academic year, high levels are 42%, medium are 32%, and low are 26%. For the 2019/2020 academic year, the high rate is 18%, medium is 59%, and low is 24%. For the 2020/2021 academic year the level of student learning strategies is high by 20%, medium is 50%, low is 30%. The reliability test for the LASSI instrument in this study was 0.8. Groups of students who have low learning strategies are influenced by habit of mind (anxiety), habit of professional (motivation) and habit of learning (test-strategies) which have not been managed properly.